2019
DOI: 10.1161/cir.0000000000000671
|View full text |Cite
|
Sign up to set email alerts
|

Water Pipe (Hookah) Smoking and Cardiovascular Disease Risk: A Scientific Statement From the American Heart Association

Abstract: Tobacco smoking with a water pipe or hookah is increasing globally. There are millions of water pipe tobacco smokers worldwide, and in the United States, water pipe use is more common among youth and young adults than among adults. The spread of water pipe tobacco smoking has been abetted by the marketing of flavored tobacco, a social media environment that promotes water pipe smoking, and misperceptions about the addictive potential and potential adverse health effects of this form of tobacco use. There is gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
91
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(117 citation statements)
references
References 135 publications
(172 reference statements)
2
91
0
4
Order By: Relevance
“…Studies assessing the similarity between cigarette smoking (CS) and WPS indicated that one daily session of WPS equates smoking of 10 cigarettes per day [3]. Moreover, it has been reported that the adverse pulmonary and systemic effects of WPS are comparable or even more marked than those of CS [4][5][6]. Several factors have been quoted to explain the significant increase in WPS use, including the misperception that it is less addictive and less harmful than CS.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies assessing the similarity between cigarette smoking (CS) and WPS indicated that one daily session of WPS equates smoking of 10 cigarettes per day [3]. Moreover, it has been reported that the adverse pulmonary and systemic effects of WPS are comparable or even more marked than those of CS [4][5][6]. Several factors have been quoted to explain the significant increase in WPS use, including the misperception that it is less addictive and less harmful than CS.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several WPS users indicated that one of the reasons for their preference of WPS over CS is that they are confident of their capacity to abandon WPS when they want and that the water filters out the toxins [7,8]. Moreover, it has been reported that the use of flavoured fruit scent waterpipe tobacco to override the formerly intolerable aroma has increased its attractiveness to first-time users, particularly teenagers [6,9,10]. In fact, youths cite the pleasant taste and smell of WPS to explain the reasons for their use of WPS [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 The American Heart Association recently stated that waterpipe smoke delivers known tobacco toxicants and carcinogens and that waterpipe smoking is associated with many of the same risks as cigarettes smoking, such as lung cancer, and respiratory and cardiovascular diseases. 4 The spread of waterpipe smoking is also perpetuated by the lag in policy and regulatory response to address it. 5 6 This is not unexpected given its special configuration and characteristics, which influence the applicability of known effective tobacco control policies to this emerging tobacco product.…”
mentioning
confidence: 99%